Factors influencing the academic success of Latinx students matriculating at 2-year and transferring to 4-year US institutions-implications for STEM majors: a systematic review of the literature - Erica R. Winterer; Jeffrey E. Froyd; Maura Borrego; Julie P. Martin; Margaret Foster (SpringerOpen, 2020)
Abstract This systematic review identifies factors that prior studies have identified as supporting the academic success of Latinx transfer students, who matriculate at 2-year institutions with respect to earning a 4-year baccalaureate degree in a STEM field. Since the students matriculate at a 2-year institution, they must, at some point in their academic career, transfer to a 4-year institution to earn the baccalaureate degree. Search and screening procedures identified 59 qualifying studies describing factors supporting persistence, transfer, or graduation of Latinx students matriculating at 2-year institutions. To synthesize findings, we coded the 31 quantitative, 22 qualitative, and six mixed methods studies according to unified themes. Nearly half the quantitative studies explored student characteristics alone, while some qualitative studies explicitly sought to identify assets Latinx students bring to higher education. None of the quantitative students utilized assets-based frameworks such as Yosso (Race Ethn Educ 8:69-91, 2005) to guide their analysis. All types of studies contributed to the conclusion that quality interactions with peers and staff support success of Latinx STEM transfer students. Specific details and strategies for institutions and their staff to support these interactions are described.